Late initiation of dialysis among women and ethnic minorities in the United States - Kausz, Annamaria T.; Obrador, Gregorio; Arora, Pradeep; Ruthazer, Robin; Levey, Andrew S.; Pereira, Brian J. G. (My University, 2000)
The ideal timing of initiation of renal replacement (RRT) therapy has been debated. It is currently recommended that RRT be instituted once the GFR falls below 10.5 ml/min per 1.73 m(2), unless edema-free body weight is stable or increased, the normalized protein nitrogen appearance rate is 0.8 g/kg per d or greater, and there are no clinical signs or symptoms of uremia. However, the mean estimated GFR at initiation of dialysis in the United States is 7.1 ml/min per 1.73 m(2). Factors that are associated with timing of initiation of dialysis in the United States are not clear. A cross-sectional study was performed to determine the factors that are associated with late initiation of dialysis as defined by GFR at initiation of less than 5 ml/min per 1.73 m(2) among patients who began dialysis in the United States between 1995 and 1997. Data were obtained from the U.S. Renal Data System, and GFR was estimated using the formula derived from the Modification of Diet in Renal Disease Study. Twenty-three percent of patients started dialysis late. In the multivariate analysis, women (odds ratio [OR] = 1.70), Hispanics and Asians (OR = 1.47 and 1.66, respectively, compared with Caucasians), uninsured patients (OR = 1.55 compared with private insurance), and employed patients (OR = 1.20) were more likely to start dialysis late. Patients with diabetes, cardiac disease, peripheral vascular disease, and poor functional status were less likely to start dialysis late compared with patients without these comorbid conditions. Certain nonclinical patient characteristics, notably female gender, race, and lack of insurance, are related to an increased likelihood of late initiation of dialysis. These factors may reflect reduced access to care. Additional studies are indicated to determine the potential impact of reduced access to care and whether late initiation of dialysis results in adverse clinical and economic outcomes among patients with end-stage renal disease in the United States. © Journal of the American Society of Nephrology